Mission as Transformation: An Exploration of the Relationship Between Mission and Development - Si, Oliver Byar Bowh (International review of mission, 2008)
This article attempts to articulate a theology that explores the relationship between mission and development. It conceptually engages in theological themes, especially the concepts of love, justice and freedom. It also discusses the meaning of missio Dei and its relation to the church. Moreover, it examines the relation between mission as liberation and Sen's philosophy of development. It is hoped that Sen's revolutionary idea of development based on the concept of “freedom” will offer a significant contribution to the understanding of a contemporary theology of mission. The essay is written from an activist theological approach to mission as transformation.